The foraging behavior of a species of bumble bee (Bombus pomorum) that became extinct in the British Isles in the nineteenth century. Issue 5 (20th October 2017) - Jeffers, Darren
Abstract : Three species of bumble bee ( Bombus spp.) are known to have become extinct in the British Isles. The first of these, Bombus pomorum was last collected (presumed extinct) in 1864. Here, I report the first direct evidence of the foraging behavior of Bombus pomorum from the analysis of pollen preserved on the hairs of the three surviving British museum specimens. The pollen removed from the bees belongs to 11 different plant families including Amaranthaceae, Apiaceae, Araliaceae, Asteraceae, Campanulaceae, Caprifoliaceae, Fabaceae, Geraniaceae, Lamiaceae, Onagraceae and Pinaceae. The diversity of the pollen taxa indicates that when present in the British Isles, Bombus pomorum adopted a generalized rather than narrow foraging strategy.